Phytol-Loaded Solid Lipid Nanoparticles as a Novel Anticandidal Nanobiotechnological Approach - Tábata L. C. Lima; Luanda B. F. C. Souza; Lannya C. S. Tavares-Pessoa; Alaine M. dos Santos-Silva; Rômulo S. Cavalcante; Raimundo F. de Araújo-Júnior; Alianda M. Cornélio; Matheus F. Fernandes-Pedrosa; Guilherme Maranhão Chaves; Arnóbio Antônio da Silva-Júnior (MDPI AG, 2020)
Phytol is a diterpene alcohol and can be found as a product of the metabolism of chlorophyll in plants. This compound has been explored as a potential antimicrobial agent, but it is insoluble in water. In this study, we describe a novel approach for an interesting anticandidal drug delivery system containing phytol. Different formulations of phytol-loaded solid lipid nanoparticles (SLN) were designed and tested using a natural lipid, 1,3-distearyl-2-oleyl-glycerol (TG1). Different compositions were considered to obtain three formulations with 1:10, 1:5, and 1:3 w/w phytol/TG1 ratios. All the formulations were prepared by emulsification solvent evaporation method and had their physicochemical properties assessed. The biocompatibility assay was performed in the HEK-293 cell line and the antifungal efficacy was demonstrated in different strains of Candida ssp., including different clinical isolates. Spherical and uniform SLN (<300 nm, PdI < 0.2) with phytol-loading efficiency >65% were achieved. Phytol-loaded SLN showed a dose-dependent cytotoxic effect in the HEK-293 cell line. The three tested formulations of phytol-loaded SLN considerably enhanced the minimal inhibitory concentration of phytol against 15 strains of Candida spp. Considering the clinical isolates, the formulations containing the highest phytol/TG1 ratios showed MICs at 100%. Thus, the feasibility and potential of phytol-loaded SLN was demonstrated in vitro, being a promising nanocarrier for phytol delivery from an anticandidal approach.